2020
DOI: 10.25079/ukhjse.v4n2y2020.pp84-100
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Tectonic Origin of the Gara and Mateen Anticlines Using Geomorphological and Structural Forms, Iraqi Kurdistan Region

Abstract: Gara and Mateen are 2 major anticlines in the northern part of the Iraqi Kurdistan Region, located in the vicinity of the town Amadiyah. Both anticlines are oriented in an almost east–west (E–W) trend with a steep southern limb. The length and width of the Gara and Mateen anticlines are 87 km and 63 km, and 11 km and 9.5 km, respectively. The 2 anticlines are separated by a wide and shallow syncline filled by the Tertiary rocks of the Pliocene–Pleistocene age. The oldest exposed rocks in the Gara and Mateen an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Le , conducted regional balanced and restored sections across the northwestern part of the Zagros Fold -Thrust Belt in the Iraqi Kurdistan Region, and considered the Bana Bawi anticline as a double plunging anticline. Sissakian et al (2018;2020a and2020b) and Ghafur et al (2019) studied several anticlines nearby to the Pirmam and Bana Bawi anticlines and concluded that the studied anticlines show similar indications for lateral growth.…”
Section: Introductionmentioning
confidence: 99%
“…Le , conducted regional balanced and restored sections across the northwestern part of the Zagros Fold -Thrust Belt in the Iraqi Kurdistan Region, and considered the Bana Bawi anticline as a double plunging anticline. Sissakian et al (2018;2020a and2020b) and Ghafur et al (2019) studied several anticlines nearby to the Pirmam and Bana Bawi anticlines and concluded that the studied anticlines show similar indications for lateral growth.…”
Section: Introductionmentioning
confidence: 99%
“…Other anticlines exhibit lateral growth mainly northwest wards. This is indicated by different geomorphological and structural features (Ghafur et al, 2019;Sissakian et al, 2020aSissakian et al, , 2020b.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite image of Gara and Mateen anticlines. Note the domes and en-echelon plunges(Sissakian et al, 2020b)…”
mentioning
confidence: 99%